Hank the Cowdog: The Case of the Perfect Dog - Book 59 - Erickson, John R. 1943- (Perryton, TX : Maverick Books, 2012)
Hank finds himself in competition with a new dog, Happy, who seems perfect until it is discovered that he will eat anything.
Unabridged.
Compact discs.
Keywords: Labrador retriever -- Fiction; Dogs -- Fiction; Humorous Stories; Audiobooks; Texas -- Fiction; Junior Fiction audiobooks